1978
DOI: 10.1104/pp.61.4.703
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Pathway of α-Ketoglutarate in Citrus Leaves as Affected by Phosphorus Nutrition

Abstract: The uptake ad metabolism of a-15-14Clketoglutarate by phospborusdeficient and full nutrient (control) iemo (Citus lmn) leaves were studied over various thme intervals. After 45 minutes In P-deficient leaves, the bulk of Incorporated 14C appeared In organk acids and much less In amino acids, while In the control leaves, the 14C contests of organic and amino acids were equal. In P-efcient leaves, after loger Incubation times the 14C content of organic acids and anino acids Increased, whRe that of CO and residue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…Unlike in the present work, P deficiency increased the concentration of citrate in rape and hedge mustard shoots, whereas the concentration of malate was affected little in hedge mustard shoots and even declined in rape shoots (Hoffland et al, 1992). In lemon leaves, the P-deficiency-induced increase in the concentration of malate was much less than that of citrate (Achituv and Bar-Akiva, 1978). In P-deficient rice leaves, the marked decrease in oxalate concentration was accompanied by increased malate and citrate concentration (Nanamori et al, 2004).…”
Section: Root Malate Concentration (µMolcontrasting
confidence: 72%
See 1 more Smart Citation
“…Unlike in the present work, P deficiency increased the concentration of citrate in rape and hedge mustard shoots, whereas the concentration of malate was affected little in hedge mustard shoots and even declined in rape shoots (Hoffland et al, 1992). In lemon leaves, the P-deficiency-induced increase in the concentration of malate was much less than that of citrate (Achituv and Bar-Akiva, 1978). In P-deficient rice leaves, the marked decrease in oxalate concentration was accompanied by increased malate and citrate concentration (Nanamori et al, 2004).…”
Section: Root Malate Concentration (µMolcontrasting
confidence: 72%
“…Achituv and Bar-Akiva (1978) showed that citrate concentration in P-deficient lemon (Citrus limon Burm.) leaves was almost 20 times higher than in controls, while P-deficiency-induced increase in malate concentration was much less.…”
Section: Introductionmentioning
confidence: 99%
“…In China, Mg-deficiency is frequently observed in Citrus plantations and is responsible for loss of productivity and fruit quality (Ling et al 2009). Previous studies showed that malate and citrate were the major OAs in both leaves (Achituv and Bar-Akiva 1978) and fruit juice (Yamaki 1989) of Citrus. In plant cells, malate synthesis mainly occurs in the cytosol and is catalyzed by phosphoenolpyruvate carboxylase (PEPC, EC 4.1.1.31) and NAD-malate dehydrogenase (NAD-MDH, EC 1.1.1.37) (Moing et al 2000).…”
Section: Introductionmentioning
confidence: 96%